PERSONAL INVESTMENT IN L2 TASK DESIGN AND LEARNING: A CASE STUDY OF TWO JAPANESE LEARNERS OF ENGLISH - Lambert, Craig; Minn, Danny (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract The present study explores ways in which personal investment might be operationalized as a condition in L2 task design, how this condition might affect L2 learning, and how the effects of the condition might be effectively measured in future empirical research. Two intermediate-level Japanese females completed three task types (instructional, narrative, opinion) in two conditions (personal investment & teacher investment). The personal investment (PI) condition required them to supply the content and resource materials on which the pedagogic tasks operated, whereas in the teacher investment (TI) condition these materials were supplied as part of the task as set. Three types of data were then triangulated in order to explore ways in which this condition may affect L2 performance and metacognition on tasks: oral performances, post-performance protocols, and questionnaires. Results indicate that performances in the PI condition contained more elaboration and more associations with existing knowledge. The condition may thus provide one means of controlling the ‘need’ component of Laufer and Hulstijn’s (2001) Involvement Load Hypothesis. The study explores the potential of tasks in L2 acquisition, providing both a heuristic and initial hypotheses for future study of relationships between this task condition, L2 performance and metacognition. Resumen Este estudio explora los modos en los que la “inversión personal” podría funcionar como una condición en el diseño de tareas en una L2, cómo afectaría esta opción al aprendizaje de la L2, y cómo los efectos de la opción podrían medirse de forma efectiva en investigaciones empíricas futuras. Dos informantes femeninas japonesas de nivel intermedio realizaron tres tipos de tareas (instrucción, narración y opinión) en dos opciones (“inversión personal” e “inversión del profesor”). La opción “inversión personal” (IP) requería que ellas proporcionasen el contenido y los materiales didácticos sobre las que se realizaban las tareas pedagógicas, mientras que en la opción “inversión del profesor” (TI) estos materiales eran proporcionados como parte de la tarea. Se triangularon tres tipos de datos obtenidos con el fin de explorar los modos en los que estas opciones podrían afectar el rendimiento en la L2 y la metacognición en las tareas: representaciones orales, protocolos posteriores a las representaciones y cuestionarios. Los resultados indican que el rendimiento en la opción IP era más elaborada y había más asociaciones con el conocimiento previo. La opción puede así proporcionar un modo de controlar el “componente necesidad” de la “Involvement Load Hypothesis” de Laufer & Hulstijn (2001). El estudio explora el potencial de las tareas en la adquisición de una L2, proporcionando tanto una hipótesis heurística como inicial para futuros estudios de las relaciones entre estas opciones de tareas, el rendimiento en la L2 y la metacognición.